The Effects of Eccentric and Plyometric Training Programs and Their Combination on Stability and the Functional Performance in the Post-ACL-Surgical Rehabilitation Period of Elite Female Athletes - Kasmi, Sofien; Zouhal, Hassane; Hammami, Raouf; Clark, Cain C. T.; Hackney, Anthony C.; Hammami, Amri; Chtara, Mokhtar; Chortane, Sabri Gaied; Salah, Fatma Zohra Ben; Granacher, Urs; Ounis, Omar Ben (Frontiers in Physiology, 2021)
Background: The standard method to treat physically active patients with ACL rupture is ligament reconstruction surgery. The rehabilitation training program is very important to improve functional performance in recreational athletes following ACL reconstruction. Objectives: The aims of this study were to compare the effects of three different training programs, eccentric training (ECC), plyometric training (PLYO), or combined eccentric and plyometric training (COMB), on dynamic balance (Y-BAL), the Lysholm Knee Scale (LKS), the return to sport index (RSI), and the leg symmetry index (LSI) for the single leg hop test for distance in elite female athletes after anterior cruciate ligament (ACL) surgery. Materials and Methods: Fourteen weeks after rehabilitation from surgery, 40 elite female athletes (20.3±3.2 yrs.), who had undergone an ACL reconstruction, participated in a short-term (6-weeks; 2 times a week) training study. All participants received the same rehabilitation protocol prior to the training study. Athletes were randomly assigned to three experimental groups, ECC (n=10), PLYO (n=10), and COMB (n=10), and to a control group (CON: n=10). Testing was conducted before and after the 6-weeks training programs and included the Y-BAL, LKS, and RSI. LSI was assessed after the 6-weeks training programs only. Results: Adherence rate was 100% across all groups and no training or test-related injuries were reported. No significant between-group baseline differences (pre-6-weeks training) were observed for any of the parameters. Significant group-by-time interactions were found for Y-BAL (p<0.001, ES=1.73), LKS (p<0.001, ES=0.76), and RSI (p<0.001, ES=1.39). Contrast analysis demonstrated that COMB yielded significantly greater improvements in Y-BAL, LKS, and RSI (all p<0.001), in addition to significantly better performances in LSI (all p<0.001), than CON, PLYO, and ECC, respectively. Conclusion: In conclusion, combined (eccentric/plyometric) training seems to represent the most effective training method as it exerts positive effects on both stability and functional performance in the post-ACL-surgical rehabilitation period of elite female athletes.